Physics ContributionsDose correction in lung for HDR breast brachytherapy - Slessinger, Eric; Pepin, Eric; Zhao, Qingya; Zhao, Li; Das, Indra (Journal of Contemporary Brachytherapy, 2012)
Purpose: To evaluate the dosimetric impact of lung tissue in Ir-192 APBI. Material and methods: In a 40 × 40 × 40 cm 3 water tank, an Accelerated Partial Breast Irradiation (APBI) brachytherapy balloon inflated to 4 cm diameter was situated directly below the center of a 30 × 30 × 1 cm 3 solid water slab. Nine cm of solid water was stacked above the 1 cm base. A parallel plate ion chamber was centered above the base and ionization current measurements were taken from the central HDR source dwell position for channels 1, 2, 3 and 5 of the balloon. Additional ionization data was acquired in the 9 cm stack at 1 cm increments. A comparable data set was also measured after replacing the 9 cm solid water stack with cork slabs. The ratios of measurements in the two phantoms were calculated and compared to predicted results of a commercial treatment planning system. Results: Lower dose was measured in the cork within 1 cm of the cork/solid water interface possibly due to backscatter effects. Higher dose was measured beyond 1 cm from the cork/solid water interface, increasing with path length up to 15% at 9 cm depth in cork. The treatment planning system did not predict either dose effect. Conclusions : This study investigates the dosimetry of low density material when the breast is treated with Ir-192 brachytherapy. HDR dose from Ir-192 in a cork media is shown to be significantly different than in unit density media. These dose differences are not predicted in most commercial brachytherapy planning systems. Empirical models based on measurements could be used to estimate lung dose associated with HDR breast brachytherapy.